2015
DOI: 10.1186/s12885-015-1197-x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment and survival of non-alcoholic steatohepatitis associated hepatocellular carcinoma

Abstract: BackgroundThe incidence of non-alcoholic steatohepatitis (NASH) is increasing worldwide and a poorly defined subset of patients develops end-stage liver disease and hepatocellular carcinoma (HCC). Differences in the biological behaviour, tumour characteristics, associated risk factors, treatment outcomes and overall survival of patients with NASH-HCC remain poorly defined. The aim of this study was to determine and analyze these differences in a large clinical cohort to guide treatment decisions.Methods1119 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
96
3
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(106 citation statements)
references
References 32 publications
6
96
3
1
Order By: Relevance
“…NASH is the most rapidly increasing indication of liver transplantation for HCC in the USA [7]. It is still undetermined whether therapeutic outcome is comparable to other liver disease etiologies [8,9]. …”
Section: Changing Landscape Of Hcc Demographicsmentioning
confidence: 99%
“…NASH is the most rapidly increasing indication of liver transplantation for HCC in the USA [7]. It is still undetermined whether therapeutic outcome is comparable to other liver disease etiologies [8,9]. …”
Section: Changing Landscape Of Hcc Demographicsmentioning
confidence: 99%
“…non-alcoholic steatohepatitis (NASH) and for the evaluation of hepatic fibrosis [77]. Moreover, it has been reported that NAFLD/NASH may progress to hepatocellular carcinoma (HCC) also in the absence of apparent cirrhosis [77,78].…”
Section: Non-alcoholic Fatty Liver Diseasementioning
confidence: 99%
“…These data support the idea that biological mechanisms and risk factors contributing to hepatocarcinogenesis in these two steatohepatitis variants are similar. In particular we found that age, Hispanic ethnicity, T2DM, and not being diagnosed with hyperlipidemia were associated with presence of HCC . While the precise age may vary, increased screening for HCC in patients with NASH and ALD starting at 60 years of age may be warranted.…”
Section: Discussionmentioning
confidence: 99%